UPAYA PENINGKATAN HASIL BELAJAR TOLAK PELURU MELALUI MEDIA BOLA PLASTIK BEKAS (Department of Physical Education, Sport, Health and Recreation, 2015)
This research is a classroom action research, the research subjects were fourth grade students of SDN 02 Pododadi totaling 29 students. Learning outcomes of the research object shot put used plastic balls through the media. When the study in the first cycle dated March 19, 2014 and the second cycle of 5 April 2014, the data collection techniques used method of observation, test methods, documentation. Instrument observation sheet, about the questionnaire. The results showed that the learning outcomes shot put with a plastic ball the former had a positive impact, as seen in the results of students' mastery learning which exceeds a predetermined KKM has increased by 75 in the first cycle in the form of mastery learning reaches 34.50%, while in the second cycle achieve mastery learning 86.20%.